Importância relativa da dispersão primária e secundária de sementes - Camargo, Paulo Henrique Santos Araújo (2014)
Seed dispersal is a key process in the reproductive cycle of plants. Diplochory is the system in which the seed dispersal is performed by a sequence of two or more stages in which often vertebrates act as primary dispersers and ants as secondary dispersers. In this work, we investigated the relative contribution of primary and secondary seed dispersal by birds and ants, respectively, for the regeneration of Erythroxylum ambiguum, a shrub of the Atlantic Forest that produces ornithochorous fruits. The study was carried out in an Atlantic rain forest in the Parque Estadual Carlos Botelho (SP) from August 2012 to April 2014. After 4163.2 hours of focal observations on 21 individuals with ripe fruit, we recorded 12 species of birds feeding on fruits (average duration of 36 s/visit). During visits about 90% of the fruits were swallowed whole and the estimated dispersal distance was 11.4 ± 6.8 m (mean ± SD of distance until the first landing perch after the visit). Comparative experiments showed greater speed and final germination percentage in the seeds removed from the bird droppings Turdus albicollis and T. leucomelas and from refuse dumps of colonies of the ant Pachycondyla striata compared to controls, indicating that these birds and ants positively affect seed germination. On average, each plant (n = 11) produced 381 ± 329 fruits. Birds removed a mean of 26% of the fruits produced, and 74% of the fruits reached the ground below plant crown (57% as ripe fruit). Most of the diaspores fallen to the ground were removed by vertebrate seed predators, while ants removed 27% of total production. Although 20 species of ants interacted with the diaspores in the soil, only five species removed the seed to a distance of 0.91 ± 0.93 m (n = 24). In addition, 60% of the seeds presented in bird feces were removed by ants. Seedlings of Erythroxylum were found more frequently in ant nests compared to controls. Thus, the system of seed dispersal of E. ambiguum is diplochorous. Although we did not found a difference in the quantitative importance between birds and ants, these animals act complementarily in seed dispersal by removing the seed from the vicinity of the parent plant and redistributing the seeds to favorable locations for seedling recruitment, respectively. Furthermore, our results suggest that although most of the fruits of the Atlantic forest are adapted to dispersal by vertebrates, ants may be as important in the dispersal of the seeds and in plant regeneration as vertebrates.